Two novel chiral tetranucleate copper-based complexes: crystal structures, nanoparticles, and inhibiting angiogenesis and the growth of human breast cancer by regulating the VEGF/VEGFR2 signal pathway in vitro. Issue 18 (22nd April 2020) - Zhang, Pei-Lu; Hou, Xiao-Xiao; Liu, Mei-Rong; Huang, Fu-Ping; Qin, Xiu-Ying
Abstract : Nano-copper-based complexes containing l -methioninol-derived Schiff bases act as an inhibitor of angiogenesis and an inducer of apoptosis to resist breast cancer in vitro . Abstract : The single crystals of two novel copper(ii )-based complexes containing l -methioninol-derived Schiff bases were obtained and characterized. The nanoparticles of these complexes were prepared and their cellular uptake was measured in MDA-MB-231 cells and HUVECs. It was found that these complexes could remarkably induce apoptosis, inhibit proliferation, suppress migration and metastasis, and inhibit angiogenesis and the growth of triple-negative breast cancer derived from MDA-MB-231 cells in vitro . Meanwhile, these complexes exhibit anticancer and antiangiogenic functions by activating the important protein molecules VEGFR2, FAK, AKT and Erk1/2 or their phosphorylated molecules p-VEGFR2, p-FAK, p-AKT, and p-Erk1/2 in the VEGF/VEGFR2 signaling pathway, collapsing the mitochondrial membrane potential, and damaging the level of reactive oxygen species.